The Contribution of Teacher-Student Attachment on Problematic Internet Use (PIU) Among High School Students - Rahmawati, Yuliana Mukti; Rahmadani, Anisa (Universitas Negeri Malang, 2024)
Teachers in schools can affect internet use among adolescent students, who have a high prevalence of accessing the internet for purposes other than educational content. This research aims to investigate the contribution of the teacher-student attachment to the problematic internet use (PIU) of high school students. The respondents came from high school students (N of 160) with a mean age of 13.8 (SD equals 1.6), and 58 percent were female. Data was collected using an accidental sampling technique. PIU is measured by self-report scale using the Indonesian Problematic Internet Use Scale (IPIUS) and teacher attachment using the Inventory of Teacher-Student Relationship (ITSR). This research applied content validity and Cronbach’s alpha. Data was collected with Google Forms and data analysis using regression analysis assisted by the SPSS software. The findings show a significant contribution from teacher-student attachment to high schools’ PIU and highlight the importance of teacher roles in the onset of behavioral problems associated with internet use. More discussion about the role of teachers in determining adolescent student behavior is suggested.